A Descriptive Analysis of the Nutraceutical Constituents, Extraction Techniques, and Possible Health Benefits of Tamarind - Wal, Pranay; Debnath, Biplab; Sarkar, Dhrubajyoti; Verma, Neha; Rathore, Shruti; Wal, Ankita (Current Traditional Medicine, 2024)
Background: Tamarind is a multifunctional tree, with nearly every portion having significant nutritional or therapeutic use. The fruit, which produces acidic pulp, is the most valuable and often utilized portion. Objective: The aim of this paper is to discuss the distribution, habitat, chemical constituents and extraction techniques of tamarind. Methods: This study reviews the chemical constituents, health benefits and extraction techniques of tamarind. Databases such as PubMed, Scopus, Science Direct, and Google Scholar were used to search articles from 1990 to 2022. The key search terms included tamarind, phytoconstituents extraction and anti-nutritional factor. Research studies also included similar plant parts extracted from similar solvents which were considered in this review. Results: According to our observations, Tamarindus indica is a crucial plant with significant pharmacological properties. It is extensively used as a conventional medicine to treat a variety of disorders; however, its active ingredients require further investigation for future drug development and pharmacological activity. Tamarind contains a diverse range of bioactive compounds, including polyphenols, flavonoids, alkaloids, vitamins, and minerals, which have been associated with various health-promoting properties. The study examines different extraction methods used to isolate tamarind's bioactive constituents, such as solvent extraction, supercritical fluid extraction (SFE), and microwave-assisted extraction (MAE). Furthermore, the research highlights the potential health benefits of tamarind, including antioxidant activity, anti-inflammatory effects, gastrointestinal support, cardiovascular benefits, and antimicrobial properties. Discussion: Tamarind includes citric acid, linoleic acid, volatile oils, vitamin C, potassium, Camp sterol, -amyrin, Tannins, saponins, and glycosides as a result of this. It has several pharmacological properties such as reducing swelling, preventing oxidation, hypolipidemic, weight loss, antibacterial, hepatoprotective, anthelmintic, and painkiller properties. These properties will assist to generate interest in Tamarind and develop novel preparations with more medicinal and commercial potential. The findings indicate that tamarind holds significant promise as a natural resource for developing functional foods, nutraceuticals, and pharmaceuticals with potential positive impacts on human health.
Keywords: antioxidant